Media Sosial Marketing pada Instagram Shopee Indonesia dan Pengaruhnya terhadap Customer Engagement serta Brand Image - Alfira, Alfira; Bharata, Wira; Sanjaya, Arwin (Institut Agama Islam Sunan Giri Ponorogo, 2021)
The high use of social media in Indonesia today is the reason why social media is widely used as a promotional strategy or what has recently been called Social Media Marketing. One company that uses Social Media Marketing is Shopee Indonesia. With content uploaded through Shopee Indonesia's Instagram, Shopee Indonesia's Social Media Marketing is effective. This can be seen through the high level of engagement on Instagram Shopee Indonesia. The purpose of this study was to determine the effect of Social Media Marketing on Customer Engagement and Band Image on Shopee Indonesia's Instagram account. The method applied in the research is quantitative. The sampling technique used is non-probability sampling. The sampling method used is purposive sampling. Based on the results of the Slovin formula, the researchers distributed questionnaires to 100 Instagram followers of Shopee Indonesia. The analytical technique used is multiple regression analysis followed by path analysis with the help of SPSS 25 software. The results show that Social Media Marketing has a positive and significant effect on Customer Engagement. Social Media Marketing has no significant positive effect on Brand Image. Customer Engagement is found to be a mediator between Social Media Marketing and Brand Image which results have a positive and significant effect. The results also explain that Customer Engagement has a positive and significant effect on Brand Image. Then Brand Image also has a positive and significant effect on Customer Engagement.